Samudera Dive Centre / Fairus Lida Khalid, Noorul Aslinda Fatiah Mat Jusoh and Noor Azean Ismail - Othman, Fairus Lida Khalid; Mat Jusoh, Noorul Aslinda Fatiah; Ismail, Noor Azean (2000)
The type of their business is Scuba Diving Centre. Samudera word means sea while Dive word refer to diving. This is partnership business. Samudera Dive Centre was establish to give a good services towards their customer in training classes and sells such as diving accessories. They did not only provide training classes, but they also sell the accessories of diving such as fin, drysuit,pockets, musk and so on. This business located at Pantai Chenang, Langkawi Kedah. The location is near our training place at Pulau Payar. It also near hotel and there are many tourist that come and interested activities while they can introduce the beautiful and unique of flora and fauna under seas of their country.